2007
DOI: 10.1016/j.lfs.2007.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Augmented behavioral response and enhanced synaptosomal calcium transport induced by repeated cocaine administration are decreased by calcium channel blockers

Abstract: Recent studies suggest that calcium influx via L-type calcium channels is necessary for psychostimulant-induced behavioral sensitization. In addition, chronic amphetamine upregulates subtype Cav1.2-containing L-type calcium channels. In the present studies, we assessed the effect of calcium channel blockers (CCBs) on cocaine-induced behavioral sensitization and determined whether the functional activity of L-type calcium channels is altered after repeated cocaine administration. Rats were administered daily in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Aberrant Ca 2+ channel activity in neurons of the reward circuitry is well established as a mechanism of cocaine action in the animal literature (41)(42)(43)(44), and genes involved in Ca 2+ regulation play a role in the pathophysiology of cocaine addiction (19). For example, in animals, Ca 2+ channel blockers decrease behavioral sensitization to cocaine and reduce cocaine-mediated synaptosomal Ca 2+ transport in the NAC (45). Cocaine-induced reward and psychological dependence behavior, as measured in the conditioned place preference paradigm, is blocked by intracerebroventricular administration of the LTCC blocker nifedipine, with this effect also reported for morphine-and methamphetamine-induced reward behavior (46).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant Ca 2+ channel activity in neurons of the reward circuitry is well established as a mechanism of cocaine action in the animal literature (41)(42)(43)(44), and genes involved in Ca 2+ regulation play a role in the pathophysiology of cocaine addiction (19). For example, in animals, Ca 2+ channel blockers decrease behavioral sensitization to cocaine and reduce cocaine-mediated synaptosomal Ca 2+ transport in the NAC (45). Cocaine-induced reward and psychological dependence behavior, as measured in the conditioned place preference paradigm, is blocked by intracerebroventricular administration of the LTCC blocker nifedipine, with this effect also reported for morphine-and methamphetamine-induced reward behavior (46).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated micro-injections of LTCC dihydropyridine agonist BayK 8644 in the VTA of rats resulted in an increased behavioral response to cocaine (Licata et al, 2000), and BayK 8644-induced stimulation of LTCCs in the caudate putamen increases extracelluar dopamine levels as measured by microdialysis (Okita et al, 2000). Additionally, it has been shown that peripheral administration of dihydropyridine antagonists attenuates sensitization to stimulants (Biala and Weglinska, 2004; Mills et al, 2007). Some data suggest that Ca v 1.2 channels are important for the behavioral expression of sensitization, but not the development of sensitization (Giordano et al, 2010; Schierberl et al, 2011).…”
Section: Function Of Cav12 In the Brain Circuits And Behaviors Ofmentioning
confidence: 99%
“…The majority of studies in animals, with a few exceptions [Schindler et al, 1995], underscored the possible role of systemic administration of LTCC antagonists in attenuating cocaineinduced rewarding effects, inhibiting cocaine-self-administration, and reducing cocaine-induced behavioral effects such as locomotor and stereotypic activity [Pani et al, 1991;Kuzmin et al, 1992;Schechter, 1993;Martellotta et al, 1994;Reimer and MartinIverson, 1994;Calcagnetti et al, 1995;Martin-Iverson et al, 1997;Mills et al, 2007]. Furthermore, Anderson et al [2008] have provided evidence that the pathophysiology of cocaine addiction could be, in part, explained by a D1 receptor-mediated activation of LTCCs in the nucleus accumbens.…”
Section: Psychostimulantsmentioning
confidence: 99%